First stable isotope and mercury assessment of bonnethead and Caribbean sharpnose sharks from a potential nursery ground in the Archipelago of Bocas del Toro, Panamanian Caribbean - Barragán-Barrera, Dalia C.; Polo-Silva, Carlos J.; González, Cindy; Rodríguez, Miguel; Baldrich, Laura; Bermúdez-Rivas, Christian; Moncaleano-Niño, Ángela Margarita; Bustamante, Paco; Caballero, Susana; Luna-Acosta, Andrea (Frontiers in Marine Science, 2024)
Bonnethead and Caribbean sharpnose sharks frequent coastal waters, rendering them vulnerable to overexploitation, with the bonnethead shark listed as endangered by the IUCN. Marine Protected Areas (MPAs) have been suggested as a management strategy to regulate shark-exploitation. Moreover, it’s essential to identify key areas where nursery grounds (NG) and adult habitats overlap to prioritize conservation zones within MPAs. Along the Caribbean Sea, several NG have been identified for larger shark species, but little is known for smaller sharks. In Bocas del Toro (BDT-Panamanian Caribbean), both bonnethead and Caribbean sharpnose sharks are distributed, with the former appearing to be genetically isolated. The local MPA in BDT doesn't include a NG identified near Solarte Island. In this study, to provide ecological information on bonnethead and Caribbean sharpnose sharks within this potential NG, we evaluated stable isotopes (δ13C and δ15N) and total-mercury (THg) values in their fins. The results revealed a higher proportion of small-adult sharks in the NG, emphasizing the necessity of conducting a comprehensive study to further characterize this area. Moreover, there was no niche-partitioning between the two species and their diets primarily consisted of small prey-items, as evidenced by the significant and negative relationship between isotopic values. Both species exhibited low THg levels in their fins. Based on these initial results and previous genetic data, it appears that BDT plays a critical role as a habitat for sharks. Thus, extending the local MPA to cover the potential NG could effectively ensure conservation of bonnethead and Caribbean sharpnose sharks in BDT.